2020
DOI: 10.5219/1211
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and weaning practices among mothers of under-five children in selected primary health care centres in Ado-Ekiti, Ekiti, Nigeria

Abstract: An appropriate diet is necessary in the growth and health status of children especially in the first two years of life. This study determined the feeding and weaning practices among mothers of children below the age of five years in two selected Primary Healthcare Centres in Ado-Ekiti, Ekiti State, Nigeria. The study design was descriptive and cross sectional using an interviewer-administered questionnaire, 200 mothers who were purposely selected participated in the study. Statistical Package for Social Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Our study shows significant association between knowledge and practices of weaning and total number of children (p-values= 0.000 and 0.000 respectively) similar to findings of research papers with p-value<0.001 5 , p-value=0.043 20 and p-value= 0.013 22 upholds this where as another. Study having p-value>0.05 18 is contrary to this.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study shows significant association between knowledge and practices of weaning and total number of children (p-values= 0.000 and 0.000 respectively) similar to findings of research papers with p-value<0.001 5 , p-value=0.043 20 and p-value= 0.013 22 upholds this where as another. Study having p-value>0.05 18 is contrary to this.…”
Section: Discussionsupporting
confidence: 89%
“…Age of children had weighty association with knowledge and practices of transitional feeding (p values= 0.000, and 0.000 respectively). Similarly, studies showed Adjusted OR=7.04 13 , p-value=0.000 20 , p-value<0.001 28 suggesting strong statistical association between these two variables. Residential status of respondent shows statistically significant association (p-value=0.028) with the overall knowledge of mothers about weaning but there is no significant association of weaning practices with it.…”
Section: Discussionmentioning
confidence: 83%
“…It has been established that malnutrition is one of the leading causes of death for many of the world's infants, accounting for over a third of the world's under-five deaths 1 – 3 . The incidence of malnutrition in the first two years of life has been directly linked with inadequate maternal breastfeeding and complementary feeding practices, along with high infectious disease levels 2 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, high prevalence (62.5%) of minimum dietary diversity attained among children 6-23 months compares well with a study from one city in India (Singhal et al 2015) which reported >70%. However, lower ranges were reported in 2018 Nigeria Demographic and Health Survey (NDHS) (22.6%) and other studies (13-46%) (NPC and ICF, 2019;Bentley et al, 2015;Mukhopadhyay et al, 2013;Mondal et al, 2014;Parashar et al, 2015). Poor dietary diversity is a common practice in poor populations because the main complementary diets are mainly starch based staples, with few animal products and vegetables (Arimond and Ruel, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Complementary feeding practices and nutritional status in Nigeria are well documented (Omotoye and Adesanmi, 2019;Sosanya et al, 2019;Ibrahim et al, 2019;Tobi et al, 2019;Oluwaseyi et al, 2019;Yusuf and Jibrin, 2020), however there is a dearth of recent evidence in Southeast Nigeria (Ayogu et al, 2015;Okereke et al, 2015;Ndiokwelu et al, 2014). Also, a good number of these local studies failed to apply either the revised WHO infant and young child feeding recommendations or the WHO 2006 growth reference in their data generation (Iheme et al, 2021).…”
Section: Introductionmentioning
confidence: 99%